دور نظم المعلومات المحاسبية في تفعيل الإفصاح المحاسبي بالقوائم المالية دراسة ميدانية - دربال خديجة (جامعة الوادي University of Eloued, 2025)
" تهدف هذه الدراسة إلى الكشف عن مدى إسهام نظم المعلومات المحاسبية في تفعيل الإفصاح المحاسبي ضمن القوائم المالية، وهذا من خلال محاولة الإجابة عن الإشكالية الرئيسية المتمثلة في إلى أي مدى يسهم استخدام نظم المعلومات المحاسبية في تحسين وتفعيل الإفصاح المحاسبي من وجهة نظر العاملين والمتخصصين في المجال المحاسبي؟ وللإجابة عن الإشكالية تم الاعتماد على المنهج الوصفي التحليلي بغية الإحاطة بالجوانب النظرية وإسقاطها على الجانب التطبيقي، وبعد جمع المعطيات باستخدام أداة الاستبانة التي وُزّعت على عينة مكوّنة من 40 مفردة من المتخصصين والممارسين في المجال المحاسبي، وقد تم تحليل البيانات باستخدام البرنامج الإحصائي (SPSS). وسعيًا لاختبار فرضيات الدراسة، توصّلت النتائج إلى أن نظم المعلومات المحاسبية تؤدي دورًا فعّالًا في تعزيز وتحسين الإفصاح المحاسبي ضمن القوائم المالية. "This study aims to explore the extent to which accounting information systems contribute to enhancing financial disclosure within financial statements. The central research question seeks to determine: To what extent does the use of accounting information systems improve and activate accounting disclosure from the perspective of professionals and practitioners in the accounting field? To address this question, the study adopted a descriptive-analytical approach in order to examine the theoretical aspects and apply them to the practical context. Data were collected using a questionnaire distributed to a sample of 40 individuals specialized in or practicing accounting. The data were analyzed using the SPSS statistical software. To test the study's hypotheses, the results revealed that accounting information systems play an effective role in enhancing and improving accounting disclosure within financial statements, thereby contributing to greater transparency and credibility in financial reporting.
ماسترالعلوم المالية والمحاسبية
Keywords: نظم المعلومات; نظم المعلومات المحاسبية; الإفصاح المحاسبي; Information Systems; Accounting Information Systems; Accounting Disclosure